2020
DOI: 10.1093/cid/ciaa928
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Is Associated With Increased Susceptibility to Influenza A (H1N1pdm) but Not H3N2 Infection

Abstract: Abstract Background Obesity has been shown to increase the risk of severe outcomes and death for influenza virus infections. However, we don’t understand the influence of obesity on susceptibility to infection or on non-severe influenza outcomes. Methods We perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…We also found that obesity significantly increased susceptibility to SARS-CoV-2. Similar associations have also been observed in a household cohort in South Africa as well as for other respiratory viruses such as influenza A H1N1pdm 15,16 .…”
Section: Discussionsupporting
confidence: 82%
“…We also found that obesity significantly increased susceptibility to SARS-CoV-2. Similar associations have also been observed in a household cohort in South Africa as well as for other respiratory viruses such as influenza A H1N1pdm 15,16 .…”
Section: Discussionsupporting
confidence: 82%
“…In this study, we did not find a significant association between BMI and influenza infection. Several studies have demonstrated that BMI is significantly associated with influenza infection or severity [ 9 12 ]. One possible explanation for this discrepancy is the difference in the study sample races.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the immune response to influenza vaccination is impaired by obesity [ 8 ]. Several epidemiological studies have reported that general obesity, defined by body mass index (BMI), is independently associated with influenza infection [ 9 12 ]. However, most of these studies included Westerners and not Asian populations.…”
Section: Introductionmentioning
confidence: 99%
“…High body mass index and low adiponectin levels are associated with reduced HCV-specific T cell responses 172 , increased liver injury 173 and poor virologic response to immune-based therapies 174 . More recently obesity has been shown to be associated with susceptibility and severity to influenza A H1N1pdm infection 175 . The microbiome influenced by diet 176,177 will also impact susceptibility and the natural course of viral infections.…”
Section: Complexities In Metabolic Responses In Individuals As a Func...mentioning
confidence: 99%